The Local Genius as Millennial Tourist Attraction in Gumbrih, Pekutatan, Jembrana, West Bali - Sirna, I Ketut; Adinegara, Gusti Ngurah Joko; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2021)
Local Genius indicates the determinants of tourist attraction from the point of view of Local genius in Gumbrih village need to be considered and well developed. The destination has the tourism attractiveness from the point of view of tourists in the village of Gumbrih needs attention to be managed properly, in determining tourist interest. Tourism Object Productivity has the facilities and infrastructure, infrastructure, and managers that support tourism activities in Gumbrih village are needed to be seriously and better developed and improved. Marketing has the product, people, process, and physical evidence need to be serious and require more attention to be managed better in order to meet the target market segment. Millennial interest has the village of Gumbrih as the choice of millennials to be able to travel, is very dominant to be maintained, because it is supported by beautiful, natural, beautiful nature and is equipped with ATV attractions, to be able to go around to the village area and gardens in the village and besides the Bali Reptile Rescue attraction, a youth-style restaurant, and a panoramic view of rice fields, forests and the echo of the waves that can be heard from these attractions.